Legal Regulation Of Leasing Contract In The Republic Of Kosovo: Array - Dauti, Arta (Acta Universitatis Danubius. Juridica, 2020)
According to the contemporary law, the contract on leasing as a legal matter is of great importance in legal circulation. The dynamic development, which characterized the leasing contract, forced the states where this contract was applied to regulate it by special legal provisions. Furthermore, in the international aspect, the leasing contract has a proper regulation pertaining the rights and obligations of the contracting parties, the lessor and the lessee. Internationally, the first convention that has foreseen and regulated the issue of leasing, is the Unidroit convention. In the Republic of Kosovo, the leasing contract is regulated by a special law, the Law of Leasing of 2009. This paper provides an insight to the legal regulation of the leasing contract in the International Convention on Financial Leasing, the legal regulation of the contract in comparative law in some large countries related to this contract, focusing on the reflection of legal regulations in the Republic of Kosovo. This paper also addresses the right and obligations of the contracting parties, the lessor and the lessee, as well as the most important types of leasing, such as leasing of consumables (consumer), investor, short-term (operating), leasing of leasing associations, concerns, local and international. We have addressed all these types of leasing in this paper. In this regard, leasing in Kosovo occupies an importnat place for implementation as a powerful mechanism for increasing the efficiency of business activities.